2017
DOI: 10.1371/journal.pone.0177227
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-E2 related factor 2 (Nrf2) on chemotherapy resistance in acute myeloid leukemia (AML) and the effect of pharmacological inhibition of Nrf2

Abstract: Cytarabine (Ara-C) and Daunorubicin (Dnr) forms the backbone of acute myeloid leukemia (AML) therapy. Drug resistance and toxic side effects pose a major threat to treatment success and hence alternate less toxic therapies are warranted. NF-E2 related factor-2 (Nrf2), a master regulator of antioxidant response is implicated in chemoresistance in solid tumors. However, little is known about the role of Nrf2 in AML chemoresistance and the effect of pharmacological inhibitor brusatol in modulating this resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
0
44
0
2
Order By: Relevance
“…Nrf2 inhibition by luteilin in oxaliplatin resistant colon cancer cells strongly had a synergistic effect with different chemotherapy drugs including oxaliplatin, doxorubicin [48] and Nrf2 suppression through Brusatol sensitized resistant acute myeloid leukemia (AML) cells to arsenic trioxide (ATO), daunorubicin (Dnr), and cytarabine (Ara-c) drugs [56]. Knocking down or silencing of Nrf2 reduced phospho-AKT, induced P27, and consequently promoted doxorubicin cytotoxicity and induced apoptosis in SKOV3 ovarian cancer cell line [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 inhibition by luteilin in oxaliplatin resistant colon cancer cells strongly had a synergistic effect with different chemotherapy drugs including oxaliplatin, doxorubicin [48] and Nrf2 suppression through Brusatol sensitized resistant acute myeloid leukemia (AML) cells to arsenic trioxide (ATO), daunorubicin (Dnr), and cytarabine (Ara-c) drugs [56]. Knocking down or silencing of Nrf2 reduced phospho-AKT, induced P27, and consequently promoted doxorubicin cytotoxicity and induced apoptosis in SKOV3 ovarian cancer cell line [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the IC50 values of oxaliplatin in SW480 and LS174T cells increased from 10. 56 (Fig.7).…”
Section: Nrf2 Suppression Caused a Reduction In Cell Survivabilitymentioning
confidence: 97%
“…Also, Karathedath et al, reported that NRF2 overexpression in AML cell lines and primary AML samples caused resistance to Cytarabine, Daunorubicin and Arsenic trioxide (ATO). Importantly, Brusatol was found to markedly decrease the NRF2 content and consequently the expression of its target genes GCLC, GCLM, HMOX-1, and NQO1, promoting ROS accumulation and apoptosis [314]. Finally, in a recent study from Xiang et al, the overactivation of NRF2 signaling was found to mediate Gemcitabine resistance in human PANC-1, PATU-8988 and BXPC3 pancreatic ductal adenocarcinoma cancer (PDAC) cell lines.…”
Section: Natural Compounds That Impair Nrf2 Signaling By Interfering mentioning
confidence: 94%
“…Nrf2 is controlled by two distinct β-TrCP recognition motifs in its Neh6 domain, one of which can be modulated by GSK-3 activity (83). Furthermore, overexpression of Nrf2, nuclear factor (erytheroid-derived-2)-like 2, increases resistance to the chemotherapeutic drug in breast cancer, acute myeloid leukemia and pancreatic cancer (84)(85)(86). However, the molecular mechanism between them remains further elucidated.…”
Section: Other F-box Proteins Involved In Chemoresistancementioning
confidence: 99%